Substitution of Dietary Sulfur Amino Acids by dl-2-Hydroxy-4-Methylthiobutyric Acid Reduces Fractional Glutathione Synthesis in Weaned Piglets. Issue 4 (27th November 2019) - Rasch, Ilka; Görs, Solvig; Tuchscherer, Armin; Viergutz, Torsten; Metges, Cornelia C; Kuhla, Björn
ABSTRACT: Background: Cys is limiting for reduced glutathione (GSH) synthesis and can be synthesized from Met. We hypothesized that the dietary Met hydroxyl analogue dl- 2-hydroxy-4-methylthiobutyric acid (dl-HMTBA ) affects Cys and GSH metabolism and oxidative stress defense differently than Met. Objective: The objective was to elucidate whether dl-HMTBA supplementation of a Met-deficient diet affects Cys flux, GSH fractional synthetic rate (FSR), and the basal oxidative stress level relative to Met supplementation in pigs. Methods: Twenty-nine male German Landrace piglets aged 28 d were allocated to 3 dietary groups: a basal diet limiting in Met (69% of Met plus Cys requirement) supplemented with either 0.15% l- Met (LMET; n  = 9), 0.15% dl- Met (DLMET; n  = 11), or 0.17% dl- HMTBA (DLHMTBA; n  = 9) on an equimolar basis. At age 54 d the pigs received a continuous infusion of [1- 13 C]-Cys to calculate Cys flux and Cys oxidation. After 3 d, GSH FSR was determined by [2, 2- 2 H2 ]-glycine infusion, and RBC GSH and oxidized GSH concentrations were measured. At age 62 d the animals were killed to determine hepatic mRNA abundances of enzymes involved in GSH metabolism, GSH concentrations, and plasma oxidative stress defense markers. Results: The Cys oxidation was 21–39% and Cys flux 5–15% higher in the fed relative to the feed-deprived state ( P < 0.001). On average, GSH FSR was 49% lower ( P < 0.01), and RBC GSH and total GSH concentrations were 12% and 9% lower, respectively, in DLHMTBA and DLMET relative to LMET pigs ( P < 0.05). In the feed-deprived state, Gly flux, the GSH:oxidized glutathione (GSSG) ratio, RBC GSSG concentrations, plasma oxidative stress markers, and the hepatic GSH content did not differ between groups. Conclusions: Although GSH FSR was higher in LMET compared with DLMET or DLHMTBA feed-deprived pigs, these differences were not reflected by lower oxidative stress markers and antioxidant defense enzymes in LMET pigs.